تحليل تأثير القطاع الصناعي على الميزان التجاري مع تغير النظام الاقتصادي في الجزائر دراسة تحليلية قياسية للفترة 1970-2022: Analysis of the impact of the industrial sector on the trade balance with the change of the economic system in Algeria an analytical and econometric study for the period 1970-2022 - موزاوي عائشة; مخلوفي عبد العالي (Journal of North African Economies, 2025)
Our goal through this research is to review the stages that the industry has gone through, and analyze its impact on the trade balance, by tracking the development of Algerian foreign trade, and highlighting the structure of the Algerian trade balance for the industrial sector, to diagnose the imbalance in the structure of the Algerian trade balance and analyze the causes of the deficit in it while highlighting the contribution of the industrial sector in the volume of exports on the one hand and highlighting the burden of this sector through the volume of imports on the other hand, where the problem of the subject was about the extent of change in the impact of the industrial sector on the trade balance In light of the transition from one economic system to another, it was studied through two axes, in which we dealt with the emergence and development of the industrial sector, analyzing its impact on the trade balance, with an econometric study to this effect we reached conclusions that the industrial sector did not live up to the industrial sector to the role for which it was established as a locomotive of the national economy and that it is one of the most important causes of the deficit in the trade balance due to the huge difference between the value of imports and the value of exports. ...and the value of exports..